Microscopic Studies and Preliminary Pharmacognostical Evaluation of Leaves and Roots of Ophiorrhiza eriantha Wight: Pharmaceutical Science-Pharmacognosy - Jaleel K, Abdul; Velraj, Malarkodi (International Journal of Life Science and Pharma Research, 2022)
Death and suffering caused by cancer have been a major concern throughout the history of mankind. Extensive research has been undertaken in the plant kingdom to find out an effective drug for the treatment of various cancer diseases. Drugs derived from plants and microorganism plays a major role in the chemotherapy of cancer. Monoterpene indole alkaloid camptothecin (CPT) is a potent anticancer agent first isolated and reported from extracts of the Chinese tree Camptotheca acuminata (Nyssaceae). Thereafter camptothecin was isolated from plants of different families mainly Ophiorrhiza mungos and Nothapodytes nimmoniana. The genus Ophiorrhiza is a potent natural source of camptothecin. The presence of fortyseven species and nine varieties of Ophiorrhiza was reported in the Indian subcontinent. Ophiorrhiza eriantha Wight is an erect subshrub species, its anticancer potential and detailed phytochemical analysis are yet to be studied. Our aim is to evaluate the pharmacognostic parameters of leaves and roots of Ophiorrhiza eriantha Wight. Our objective is to identify characteristic microscopic features of leaves and roots of the plant and to study the quantitative microscopy, ash value, loss on drying, phytochemical screening, fluorescence analysis, and powder analysis of leaf and roots of Ophiorrhiza eriantha Wight. The thickness of the midrib, lamina, leaf margin, and epidermal trichome is measured. It showed the presence of paracytic stomata. Non-glandular epidermal trichomes are common in leaf powder. Ophiorrhiza eriantha Wight is a promising anticancer plant; this is a pioneer work to explore the anatomical features of Ophiorrhiza eriantha Wight. Keywords: ,, , , And